Contextual factors that influence quality improvement implementation in primary care: The role of organizations, teams, and individuals. Issue 3 (July 2018) - Shea, Christopher M.; Turner, Kea; Albritton, Jordan; Reiter, Kristin L.
Abstract : Background: Recent emphasis on value-based health care has highlighted the importance of quality improvement (QI) in primary care settings. QI efforts, which require providers and staff to work in cross-functional teams, may be implemented with varying levels of success, with implementation being affected by factors at the organizational, teamwork, and individual levels. Purpose: The purpose of our study was to (a) identify contextual factors (organizational, teamwork, and individual) that affect implementation effectiveness of QI interventions in primary care settings and (b) compare perspectives about these factors across roles (health care administrators, physician and nonphysician clinicians, and administrative staff). Methods/Approach: We conducted semistructured interviews with 24 health care administrators, physician and nonphysician primary care providers, and administrative staff representing 10 primary care practices affiliated with one integrated delivery system. Results: Participants across all roles identified similar organizational- and team-level factors that influence QI implementation including organizational capacity to take on new initiatives (e.g., time availability of physicians), technical capability for QI (e.g., data analysis skills), and team climate (e.g., how well staff work together). There was greater variation in terms of individual-level factors, particularly perceived meaning and purpose of QI. Perceptions about value of QI ranged from positive impacts on patient care and practice competitiveness to decreased efficiency and distractions from patient care, but differences did not appear attributable to role. Conclusions: Successful QI implementation requires effective collaboration within cross-functional teams. Additional research is needed to assess how best to employ implementation strategies that promote cross-understanding of QI among team members and, ultimately, effective implementation of QI programs. Practice Implications: Health care managers in primary care settings should strive to create a strong teamwork climate, reinforced by opportunities for staff in various roles to discuss QI as a collective.